ANAPHYLACTIC SHOCK CAUSED BY SUBCUTANEOUS IMMUNOTHERAPY WITH THE ALLERGEN AMBROSIA ELATIOR – CASE REPORT - Dimitrijević, Milan; Plavšić, Aleksandra; Kusić, Nataša; Vesna Tomić Spirić, Vesna Tomić Spirić (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Sensitization to ragweed pollen can lead to symptoms of allergic rhinitis, conjunctivitis, and allergic asthma. Allergen immunotherapy (AIT) is an immunomodulatory therapeutic procedure that, in addition to short-term curative effect (reduction of disease symptoms), also has a long-term preventive effect (preventing the progression of allergic rhinitis into allergic asthma and/or preventing the development of a more severe form of the disease). The two main AIT administration modalities used in clinical practice are subcutaneous allergen immunotherapy (SCIT) and sublingual allergen immunotherapy (SLIT). Both modalities are equally effective in reducing disease symptoms, but the use of SCIT is associated with a higher risk of local and systemic adverse reactions.Case report: A patient who developed a clinical picture of anaphylactic shock during the induction phase of SCIT with Ambrosia elatior pollen extract is presented in this article. The clinical course is described as well as the quick and effective therapeutic management of this life-threatening condition.Conclusion: When properly dosed, in a medical facility and under medical supervision, SCIT with Ambrosia elatior is a very safe and well-tolerated treatment option for allergic rhinitis. Local reactions at the site of subcutaneous administration occur more often than systemic adverse reactions. Anaphylactic shock is the most severe form of a systemic allergic reaction that affects multiple organ systems and can end in death, usually due to airway obstruction and cardiovascular collapse. It is necessary to educate the medical staff as well as the patients regarding the proper treatment of this difficult condition. Based on the assessment of risk factors in each patient, severe reactions to SCIT can be predicted and avoided with appropriate precautions and prophylactic measures. Future innovations in AIT are expected to further improve the efficacy and safety of this form of treatment for allergic diseases.
Keywords: allergen immunotherapy; SCIT; anaphylactic shock; ambrosia